Des élèves de 9-12 ans de l'école primaire française et l'évolution des espèces vivantes - CORINNE JÉGOU-MAIRONE (Metaichmio Publications, 2011)
Teaching the evolution of the living species, a key concept in modern biology, is today at the heart of many studies within the French and international educational systems, from primary school to university. It may indeed go against religious beliefs and thus stir up controversy. In some cases, these beliefs may even become an obstacle to the learning of this concept. A compulsory element in the French primary curriculum until 2008, it seems however that this concept hasn't been given much importance in schools. Firstly, we shall study the official requirements in the primary curriculum and we shall identify institutional expectations. Secondly, a written questionnaire will aim to define the personal relationship primary teachers in Keystage 3 (year 4, 5, 6 at primary level) and student teachers have with the concept of evolution, inside and outside the classroom, and how this relationship might influence their decision to teach or not evolution, or the way they would teach it (Mairone, 2007; Mairone & Dupin, 2007, 2008). Thirdly, a written questionnaire submitted to Keystage 3 pupils will enable us to disclose their representations on the questions of the emergence and evolution of the living species; it will help to define learning barriers and appropriate didactic engineering. This is the subject of this proposition. This whole study is meant to make recommendations for teaching/learning of evolution of living species for primary school and for teachers training.